Geochemical records in subaerial exposure environments in Croatia using discriminant function analysis of bauxite data - Ilijanić, Nikolina; Kovačević Galović, Erli; Gizdavec, Nikola; Ivkić Filipović, Ivona; Miko, Slobodan; Peh, Zoran (Frontiers in Earth Science, 2023)
Croatian bauxites are long known for their chemical and physical diversity arisen from their characteristic origin and emplacement within the area of the Adriatic–Dinaric carbonate platform (ADCP). They include eight horizons spanning the period between the Upper Triassic (Carnian) and the Miocene, being formed on subaerially exposed platform paleoenvironments. The bauxite genesis is recorded in the bauxite geochemical composition as a unique signature of tectonostratigraphic evolution of the different parts of the Croatian Karst, including, for example, the forebulge unconformity typical for the Istrian area. In this work, explanation of the typical patterns of bauxite formation is based on the construction of a discriminant function model (DFM) resulting from the compositional data (CoDa) analysis of bauxite geochemical data (major and trace elements). The model shows that the greatest part of the variation contained in the analyzed bauxite data (the first discriminant function, DF1) is associated with systematic alteration of geochemical composition in time emphasizing characteristic decrease in clay component and gradual enrichment in heavy metals from oldest (Upper Triassic) to the youngest (Miocene) bauxites. In the general scheme, particular bauxite horizons represent standalone groups (Upper Triassic) while others form clusters showing increase and/or decrease of particular set of elements signaling the changes in environmental conditions during the considered geological history of ADCP. Other discriminant functions (DF1 and DF2) also contribute to the all-inclusive distinction between the eight a priori defined bauxite groups discriminated by the characteristic set of geochemical variables.